Collision-induced stimulated photon echo at the transition 0–1 in ytterbium: application to depolarizing collisions. (13th December 2016) - Rubtsova, N N; Gol'dort, V G; Khvorostov, E B; Kochubei, S A; Reshetov, V A
Abstract: A new idea based on the collision-induced stimulated photon echo in the presence of weak longitudinal magnetic field is applied to the depolarizing collisions research in a gaseous mixture of ytterbium vapour with xenon. Comparison of experimental data with theoretical prediction for the collision-induced stimulated photon echo in the weak magnetic field shows that the alignment decay rate of state 3 P1 in 174 Yb is higher than the orientation decay rate.